Identification of tourism supporting components based on the 7A concept in natural tourism destinations in Pangkalpinang city - Zulkia, Dwi Rizka; Maulani, Desi; Santika, Marisa (Universitas Merdeka Malang, 2025)
The development of natural tourism in urban areas is one of the important strategies in supporting ecosystem balance and improving the quality of life of the community. This study aims to identify the supporting components of tourism based on the 7A concept which includes attraction, accessibility, amenities, activities, ancillary services, available packages, and awareness, in two natural tourist destinations in Pangkalpinang City, namely Pasir Padi Beach and Tuatunu Urban Forest. The method used is qualitative descriptive through field observation, visual documentation, analysis of planning documents and analysis of tourism development based on 7A Concepts. The results of the study show that Pasir Padi Beach has advantages in terms of accessibility and facilities, but still requires improvement in sustainable management and promotion. Meanwhile, the Tuatunu Urban Forest has strong ecological and educational potential, but it is limited in terms of infrastructure, accessibility, and supporting facilities. Development strategies that involve local governments, business actors, and the community collaboratively are needed to realize sustainable and competitive natural tourism destinations, as well as support the socio-economic welfare of the community in Pangkalpinang City.